G202(P) A Survey of Necrotising Enterocolitis at a Tertiary Neonatal Unit. (4th June 2013) - Wilcock, A; Victor, S
Abstract : Aims: Necrotising enterocolitis (NEC) is a gastrointestinal emergency occurring in approximately 1–3% of neonates admitted to intensive care units. It carries significant mortality (up to 50%) and an extensive range of short and long term complications. Despite decades of research, its pathogenesis remains poorly understood, though current understanding suggests a multi-factorial aetiology. Indeed, prematurity, feeding practises, genetics, various maternal factors and certain neonatal morbidities have all been implicated in the pathogenesis of NEC. As there is a paucity of published surveys providing a general overview of NEC in the last decade, we aimed to provide a more current perspective in a tertiary neonatal unit. Methods: Using diagnostic criteria outlined in the 11th BPSU Annual Report, 49 infants with NEC within a 13 month period were retrospectively identified. Subsequently, data from patient records (including maternal data) and imaging reports was extracted and analysed. The presence of various risk factors (including those mentioned above) and information regarding the presentation, diagnosis and management of NEC in these infants were recorded along with complication and mortality rates. Results: Risk factors including intrauterine growth restriction (18.4%), patent ductus arteriosus (51%) and gastroschisis (10.2%) were highly prevalent within our cohort. Consistent with previous literature, 86% of infants were premature and 71.4% were very low birthweight infants (<1500g). However, 24.5% of infants were from multiple pregnancies which was higher than expected. Intriguingly, whilst the majority of infants (75.5%) were exclusively fed with breast milk initially, by the time NEC was diagnosed this proportion had reduced dramatically (32.7%). Gaseous distension was the most commonly seen radiographic feature (87.8%) whilst 36.7% received surgical interventions with nearly all undergoing laparotomy. Gut-related complications were observed in 20.4% of patients at discharge. Conclusion: This survey provides a more current insight into the progression of NEC from predisposing factors to current management and complications. In agreement with previous studies, no risk factor was uniformly observed. Of particular interest, however, is the trend regarding breast milk feeding. As breast milk has been shown to play a protective role in NEC, it is therefore imperative that support is offered to mothers to encourage continuation of breast milk feeding.